2015
DOI: 10.1007/s11164-015-2199-7
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles using Solanum indicum L. and their antibacterial, splenocyte cytotoxic potentials

Abstract: Green synthesis of silver nanoparticles was carried out using Solanum indicum L. plant extract as a reducing agent. The morphology of the AgNPs was determined by transmission electron microscopy. Scanning electron microscopy and energy-dispersive spectroscopy (EDX) were used to characterize the nanoparticles obtained from S. indicum L. The EDX analysis of the nanoparticles dispersion, using a range of 2-4 keV, confirmed the presence of elemental silver, without any contamination. The green synthesized AgNPs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 17 publications
4
22
0
Order By: Relevance
“…The values of these peaks indicate the characteristic of AgNPs. The results of different studies in literature interpreted these peaks as AgNPs (Sengottaiyan et al 2016;Khan et al, 2018). In accordance with this data, the crystal size of AgNPs was calculated 22.11 nm.…”
Section: Discussionmentioning
confidence: 97%
“…The values of these peaks indicate the characteristic of AgNPs. The results of different studies in literature interpreted these peaks as AgNPs (Sengottaiyan et al 2016;Khan et al, 2018). In accordance with this data, the crystal size of AgNPs was calculated 22.11 nm.…”
Section: Discussionmentioning
confidence: 97%
“…With advances in nanobiotechnology, biological synthesis of AgNPs has been proposed as an alternative to physical and chemical processes and offers budding opportunities for eco-friendly synthesis of AgNPs. Several biological materials, such as microorganisms, plant extracts and milk have been used for the synthesis of AgNPs , Ananda Babu and Gurumallesh Prabu 2011, Lee et al 2013, Otari et al 2012, Sengottaiyan et al 2015, Venkatpurwar and Pokharkar 2011. Numerous studies reported the potential application of these biologically synthesized AgNPs in different scientific fields (Kim et al 2007, Sun et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the biosynthesis of AgNPs gained considerable attention in the past decade owing to their perceived technological importance and environmental benefits [4]. Several natural resources like plant extracts [5], microorganisms [6], milk [7], oilcake [8], and panchakavyam [9] have been explored for the biological synthesis of AgNPs. Among the biological routes, plants based AgNPs synthesis gained more attention due to their rapid formation, easy handling, and large-scale production.…”
Section: Introductionmentioning
confidence: 99%